Consumers' knowledge, attitude, and behavior towards antimicrobial resistance and antimicrobial use in food production in China - Qianyun Ding; Jiuzhi Gao; Xianfeng Ding; Dan Huang; Dan Huang; Yunfeng Zhao; Yunfeng Zhao; Min Yang; Min Yang (Frontiers in Public Health, 2022)
BackgroundAntimicrobial resistance (AMR) can be induced by overuse or misuse of antimicrobials. Few researches were involved in consumers' knowledge and attitude toward antimicrobial use (AMU) in food production. This study was designed to investigate the knowledge and awareness, perception, and attitude of Chinese consumers toward AMU in food production. Their behavior, purchase intention of antimicrobial-free food products, and confidence in information sources were also investigated.MethodsAs a descriptive cross-sectional study, an online electronic survey questionnaire was conducted between February 25 and March 8, 2022, involving 1,065 consumers in China. Factor analysis was conducted to identify underlying patterns of the attitudes and information sources. Spearman correlations were employed to determine the relationship between knowledge, attitudes and the intention to pay extra. The differences in knowledge and attitudes were performed by independent t-test and one-way analysis of variance (ANOVA) test, and the difference in intention was performed by Chi-square test, when compared with demographic factors.ResultsThe findings showed that even though 75.0% of them heard of AMR, and 48.2% knew the definition of AMR, the level of consumers' knowledge of AMU in farming production and food regulations in China was not high (48.9% of participants replied correctly). About half viewed AMU and AMR as a potential risk to their health. Of these participants, 61.3% claimed that they were more likely looking for specific information about AMU on food packaging, and 58.3% changed their eating or cooking habits due to the concern. In addition, 79.8% were willing to pay extra for antimicrobial-free food products. Information sources from professionals and authorities were considered more accurate than those from media, the internet, word of mouth, and others.ConclusionsChinese consumers had insufficient knowledge and neutral attitudes about AMU in farming production and food regulations in China. A large proportion of the participants were willing to purchase antimicrobial-free food products. Most of them obtained related information from the media. This study highlighted the importance of updated education and effective communication with consumers in China. It helps to develop the reliable foodborne AMR surveillance system along food chain and improve government communication and consumer awareness.